ОЦІНКА ВПРОВАДЖЕННЯ ДИСКРЕТНОЇ СИСТЕМИ ОПАЛЕННЯ НАСЕЛЕНОГО ПУНКТУ ЕКСПРЕС-МЕТОДОМ 3Е - Demchenko, V.G.; Trubachev, A.S.; Hron, S.S. (Institute of Engineering Thermophysics of NAS of Ukraine, 2019)
The energy system of Ukraine, as well as the world power industry now in a phase of change related to the deterioration of the environment, a large number of new technologies and a change in global geopolitics. Thus, there is a need for quick decision-making when introducing new products, technologies and methods. The article proposes a modern approach to solving key strategic issues at the enterprise. A comparative analysis of existing classical methods of making management decisions is made and a number of advantages of the author's method are revealed. In this article, with the help of the proposed method, the feasibility of introducing a discrete heating system in the village is determined. In order to achieve this goal, the structure of the heat sources used in the settlement is determined, an analysis of the users of heating and comparison of the prices for heat energy is obtained using natural gas, pellets and a discrete heating system. The next step is to compare all sources of heat energy by the three main weighting criteria that most accurately reflect their quality. The preliminary expression of each criterion in a numerical dimensionless expression allows us to obtain a decision to make an optimal decision by graph-analytical method. This allows us to determine the main factors influencing the object of research and the decision making decision to three equally weighted coefficients: energy, ecology, economics. The obtained indicators are the faces of a triangular diagram, which forms the general plane within which all investigated objects or processes are located. The next step is to determine the field of satisfactory results, which has a flexible system of construction, which accurately shows the limits, taking into account the conditions of a specific task and goals. The triangular diagram has a visually accessible structure, so it is easy to understand to untrained people. As can be seen from the rating, the use of mobile heat supply with mobile battery is the most advantageous. Sources of heat supply on wood used as fuel, the most attractive from an economic point of view, however, lose to other sources of heat from the ecological and energy point of view.